Atmospheric Chemistry of n-C6F13CH2CHO: Formation from n-C6F13CH2CH2OH, Kinetics, and Mechanisms of Reactions with Chlorine Atoms and OH Radicals - Chiappero, Malisa Susana (2010)
Smog chamber FTIR techniques were used to measure k(Cl + n-C 6F13CH2CHO) = (1.84 ± 0.22) -10 -11, k(Cl + n-C6F13CHO) = (1.75 ± 0.70) - 10-12, and k(OH + n-C6F13CH2CHO) = (2.15 ± 0.26) - 10-12 cm3 molecule-1 s-1 in 700 Torr of N2 or air diluent at 296 ± 2K. The chlorine-atom-initiated oxidation of n-C6F13CH 2CH2OH in air gives n-C6F13CH 2CHO in a molar yield of 99 ± 8%. The atmospheric fate of n-C6F13CH2C(O) radicals is reaction with O 2, while the fate of n-C6F13C(O) radicals is decomposition to give n-C6F13 radicals and CO. The results are discussed with respect to the atmospheric chemistry of fluorinated alcohols and the formation of perfluorocarboxylic acids.